Phoenician-influenced metallurgy in central Portugal. Three socketed arrowheads with spur from Monte Figueiró (Ansião) - Raquel VILAÇA; Carlo BOTTAINI; Ana Margarida ARRUDA (Zephyrus, 2020)
This paper presents the results of a study carried out on three previously unpublished Iron Age socketed arrowheads with spur from Monte Figueiró –Central Portugal–, a site located between the Tagus and Mondego rivers. This region is of the utmost importance to understanding how Mediterranean influences penetrated along the Iberian Atlantic coast and up to the inland Portuguese territories, through Phoenician traders, since the Early Iron Age –8th century bc–. The socketed arrowheads with spurs, originally produced in the South-eastern end of Europe, namely in the Black Sea area, are virtually unseen in the Portuguese territory, where only another similar item has been found at Castro Marim –South Portugal–, in contrast with Spain, more specifically with the Guadalquivir region, where they are quite frequently found. Therefore, the occurrence of the three socketed arrowheads from Monte Figueiró is a challenging discovery, since Central Portugal is a peripheral area with respect to the Iberian regions that underwent an actual Phoenician colonisation. Based on this assumption, this paper will not focus just on typological and technological issues, but it will go a bit further, also reflecting on what these three artefacts can reveal about the interaction between indigenous inland communities from Central Portugal and Phoenician traders.